Analisis Faktor Penentu TPAK Berbasis Gender di Lampung (2018-2023) - Fajrina, Aqila Diva; Ananta, Prayudha; Usman, Moneyzar; Ratih, Arivina; Wahyudi, Heru (CV. ITTC INDONESIA, 2025)
This research aims to analyze the influence of Average Years of Schooling, District/City Minimum Wage, Gender Empowerment Index, Gender Development Index, and Economic Growth on the Labor Force Participation Level of men and women in 15 Districts/Cities of Lampung Province in the 2018-2023 period. This research uses panel data processed using the Random Effect Model (REM) method with strong standard errors in STATA software. The results of the research show that the average length of schooling has a significant negative effect on the male labor force participation rate, but not significantly on the female labor force participation rate. The Regency/City Minimum Wage has a significant positive influence on the Labor Force Participation Rate of men and women. The Gender Empowerment Index and Gender Development Index have a positive but not significant influence on the Labor Force Participation Levels of men and women. Meanwhile, Economic Growth has a positive but not significant effect on the male Labor Force Participation Rate, while on the female Labor Force Participation Rate, Economic Growth has a significant negative effect. Based on these findings, the government is expected to be able to provide educational effectiveness in improving the quality of the workforce and ensuring wage policies are in line with economic needs. In addition, gender empowerment programs need to be discussed in order to have a more significant impact on women's work participation.